Cytotoxic Activity of Chromolaena odorata Leaf Extract on WiDr Colon Cancer Cells - Anam, Hairul; Aswad, Hijral; Irma, Ade; Wahdaniar (Journal of Biomedical Sciences and Health, 2026)
Background: Colorectal cancer (CRC) remains the third most commonly diagnosed cancer and the second leading cause of cancer-related mortality worldwide. In 2020, CRC accounted for approximately 1.9 million new cases and over 935,000 deaths globally. Conventional chemotherapy is frequently limited by systemic toxicity and drug resistance, necessitating the identification of novel plant-derived bioactive compounds. Chromolaena odorata (Asteraceae), a tropical medicinal plant, has demonstrated pharmacological properties including wound healing and anti-inflammatory activity; however, its antiproliferative potential against colorectal cancer cells remains insufficiently explored. Objective: This study aimed to evaluate the cytotoxic and antiproliferative effects of C. odorata n-hexane leaf extract on WiDr human colorectal adenocarcinoma cells using an in vitro MTT assay. Methods: Dried leaves of C. odorata were extracted via n-hexane maceration. WiDr cells were cultured in DMEM supplemented with 10% FBS and antibiotics. Cells were treated with graded extract concentrations (62.5–1000 μg/mL) for 24 hours in triplicate. Cell viability was assessed by the MTT assay and the half-maximal inhibitory concentration (IC₅₀) was determined via nonlinear regression analysis. Results: The extract exhibited concentration-dependent cytotoxicity against WiDr cells. The highest mean inhibition rate (94.3 ± 10.7%) was observed at 1000 μg/mL. The calculated IC₅₀ value was 149.09 ± 20.91 μg/mL, indicating moderate cytotoxic potency consistent with the National Cancer Institute (NCI) classification for biologically active crude extracts (IC₅₀ < 200 μg/mL). Conclusion: Chromolaena odorata n-hexane leaf extract demonstrates significant in vitro antiproliferative activity against WiDr colorectal cancer cells. The cytotoxic activity likely involves lipophilic bioactive compounds, including terpenoids. These findings support further bioassay-guided fractionation, mechanistic investigation, and in vivo validation as potential candidates for anticancer drug development.